Preoperative assessment of patients for major vascular surgery. Issue 5 (May 2019) - Durrand, James W.; Danjoux, Gerard R.
Abstract: Effective preoperative evaluation of patients prior to major vascular surgery remains a significant multidisciplinary challenge. Focussed preoperative evaluation targeted to organ systems can mitigate the combined effects of inherently high-risk surgical procedures undertaken in a patient population with well-recognized comorbidity. Careful history and examination, supported by appropriate investigations and specialist input, remains the cornerstone of this process, with risk increasingly quantified by dedicated scoring systems. In addition, the objective assessment of functional capacity is now common in UK units with cardiopulmonary exercise testing widely employed and considered a 'gold standard' by many. When employed in a timely manner, complete preoperative assessment allows more informed perioperative decision-making, frank discussion of risk with the patient and effective utilization of critical care resources if required.